2018
DOI: 10.1002/yea.3310
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts of the soil – obscure but precious

Abstract: Pioneering studies performed in the nineteenth century demonstrated that yeasts are present in below‐ground sources. Soils were regarded more as a reservoir for yeasts that reside in habitats above it. Later studies showed that yeast communities in soils are taxonomically diverse and different from those above‐ground. Soil yeasts possess extraordinary adaptations that allow them to survive in a wide range of environmental conditions. A few species are promising sources of yeast oils and have been used in agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 102 publications
5
98
0
1
Order By: Relevance
“…The ecology of this group is very diverse. In addition to species associated with sugary substrates (Pozo, Herrera & Bazaga, ; Lievens et al, ), members of the Saccharomycetaceae have been found in soil (Treseder & Lennon, ; Yurkov, ), on plant surfaces (Boynton & Greig, ), in the gut of insects (Blackwell, ), on vertebrate skin (Underhill & Iliev, ; Limon, Skalski & Underhill, ), and in marine and frozen environments (Bass et al, ; Amaretti et al, ; Richards et al, ; Martorell et al, ; Rämä et al, ). Many have been isolated from industrial fermentations, including contaminants of food products and alcoholic fermentations (Hittinger, Steele & Ryder, ), sorbitol (Louis et al, ) and pure hydrocarbons (Buddie et al, ).…”
Section: The Yeast Lifestylementioning
confidence: 99%
See 1 more Smart Citation
“…The ecology of this group is very diverse. In addition to species associated with sugary substrates (Pozo, Herrera & Bazaga, ; Lievens et al, ), members of the Saccharomycetaceae have been found in soil (Treseder & Lennon, ; Yurkov, ), on plant surfaces (Boynton & Greig, ), in the gut of insects (Blackwell, ), on vertebrate skin (Underhill & Iliev, ; Limon, Skalski & Underhill, ), and in marine and frozen environments (Bass et al, ; Amaretti et al, ; Richards et al, ; Martorell et al, ; Rämä et al, ). Many have been isolated from industrial fermentations, including contaminants of food products and alcoholic fermentations (Hittinger, Steele & Ryder, ), sorbitol (Louis et al, ) and pure hydrocarbons (Buddie et al, ).…”
Section: The Yeast Lifestylementioning
confidence: 99%
“…Yeasts can also be found in association with surfaces of both vertebrates and invertebrates (see Section V). Fungi with a yeast lifestyle can be found in virtually any soil type, and even though their abundance tends to be relatively low, their diversity is considerable (Treseder & Lennon, ; Tedersoo et al, ; Yurkov, ).…”
Section: The Yeast Lifestylementioning
confidence: 99%
“…One of the biggest questions in ecology is how diversity is maintained in ecosystems (Hutchinson, 1959). As with biodiversity in general, yeast diversity is broad across nearly every imaginable ecosystem (Buzzini, Turchetti, & Yurkov, 2018;Carbonetto, Ramsayer, Nidelet, Legrand, & Sicard, 2018;Chappell & Fukami, 2018;Stefanini, 2018;Yurkov, 2018). The current understanding of killer yeasts' impacts on diversity is based mostly on mathematical models, and only a few hypothesis-driven observational studies have addressed killer yeasts' impacts on diversity in nature.…”
Section: How Do Killer Yeasts Influence Yeast Diversity?mentioning
confidence: 99%
“…Saccharomyces yeasts are also a single clade in the diverse polyphyletic group of yeasts (singlecelled fungi that reproduce by budding or fission; Kurtzman, Fell, & Boekhout, 2011). These diverse yeasts inhabit floral nectar, extreme environments, soils, and insect bodies, among many other habitats (Buzzini, Turchetti, & Yurkov, 2018;Chappell & Fukami, 2018;Stefanini, 2018;Yurkov, 2018). One challenge of environmental yeast sampling is to minimize sampling biases so researchers can assure that observed diversity patterns are not artefacts of their chosen sampling strategy.…”
Section: Introductionmentioning
confidence: 99%